Pattern Recognition and Machine Intelligence 5th International Conference, PReMI 2013, Kolkata, India, December 10-14, 2013. Proceedings - Maji, Pradipta; Ghosh, Ashish; Murty, M. Narasimha; Ghosh, Kuntal; Pal, Sankar K.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 5th International Conference on Pattern Recognition and Machine Intelligence, PReMI 2013, held in Kolkata, India in December 2013. The 101 revised papers presented together with 9 invited talks were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on pattern recognition; machine learning; image processing; speech and video processing; medical imaging; document image processing; soft computing; bioinformatics and computational biology; and social media mining.
Pattern recognition -- Machine learning -- Image processing -- Speech and video processing -- Medical imaging -- Document image processing -- Soft computing -- Bioinformatics and computational biology -- Social media mining.
Keywords: Computer science; Data mining; Artificial intelligence; Optical pattern recognition; Bioinformatics; Computer Science; Computation by Abstract Devices; Artificial Intelligence (incl. Robotics).; Pattern Recognition; Information Systems Applications (incl. Internet).; Data Mining and Knowledge Discovery; Computational Biology/Bioinformatics.